(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Internet technology has made E-learning a crucial tool that educational institutions all aroundthe world are putting into practice. Education and teaching methods have become much more diverse as aresult of technological and scientific advancements. An increasing number of new technologies havemade education both more efficient and personalized, as well as scientifically based and far morepowerful. Education may be provided in a different way through online learning. Advanced learners areable to skip or speed redundant training, but novices are hindered by content, removing their ownbarriers to learning. Students’ academic accomplishment is a major focus of this study, which examinesthe role of online learning and conventional learning material preparation and presentation devices, appsas well as various educational philosophies used in education.